Rhesus macaques (Macaca mulatta) with self‐injurious behavior show less behavioral anxiety during the human intruder test. Issue 1 (10th June 2016) - Peterson, Emily J.; Worlein, Julie M.; Lee, Grace H.; Dettmer, Amanda M.; Varner, Elana K.; Novak, Melinda A.
Abstract : Self‐injurious behavior (SIB) has been linked to anxiety in the human literature, but relatively few studies have explored this link in rhesus macaques. A widely used behavioral assessment of anxiety, the human intruder test (HIT), employs the mildly stressful stimulus of an unfamiliar experimenter to assess anxious behavior in macaques. The HIT was conducted on 59 (20 male) laboratory housed rhesus macaques, 30 with a record of SIB (10 male). If monkeys with SIB have a more anxious phenotype, they should show stronger reactions to the HIT. However, contrary to our predictions, monkeys with SIB did not show higher levels of anxious behavior compared to controls. They spent significantly less time showing anxious behavior and displayed little aggression in response to the stare of the intruder. SIB and control monkeys did not differ in a range score (number of unique behaviors expressed per phase); however, SIB monkeys had a lower change score (total number of behaviors expressed including repetitions) than controls. In general, monkeys that paced regardless of SIB status, showed a reduction in pacing when the intruder entered the room. Possible explanations for the failure of SIB monkeys to show increased anxiety in the HIT include greater exposure of SIB monkeys to unfamiliar humans because of their condition, evidence for a subtype of SIB which is not anxiety related, and/or the presence of comorbid depressive‐like symptoms. Am. J. Primatol. 79:e22569, 2017. © 2016 Wiley Periodicals, Inc.